ATOS study: effectiveness and safety of insulin glargine 300 U/mL in the real world clinical practice in insulin-naïve type 2 diabetic patients in the Russian Federation - Gagik R. Galstyan (Alʹmanah Kliničeskoj Mediciny, 2022)
Rationale: Basal insulin glargine 300 U/mL (Gla-300) is a second-generation basal insulin analogue that has comparable efficacy and lower variability compared to the first generation long-acting insulin analogue glargine 100 U/mL.